(Re)defining outsourcing in education. Issue 2 (3rd March 2020) - Sperka, Leigh
ABSTRACT: In this paper, I (re)define outsourcing in a way that reflects the nature of the practice in education. While business and management definitions of outsourcing have been generative to this point, they are relatively broad and place wide boundaries on the practice. Moreover, they do not acknowledge the interpretation and enactment of outsourcing in contexts where economic models were never supposed to dominate. To create a bespoke and 'stipulative' definition that is a better fit-for-purpose, I selected one school subject, Health and Physical Education (HPE), and one country, Australia, as an illustrative case. I then analysed three literature corpora to find examples and attributes of outsourcing. I argue that recruiting this new definition will allow scholars within and beyond the field of HPE to construct new arguments and generate different types of rich data on the practice in ways that they might not necessarily have been able to previously.